Republic of Madagascar : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Madagascar. (IMF Staff Country Reports; Country Report, 2020)
A further deterioration of the global environment and a deepening of the impact of the COVID-19 pandemic have worsened the macroeconomic outlook significantly, with growth now projected to be negative in 2020. As a result, urgent balance of payments needs arising from the pandemic are now estimated at 4.2 percent of GDP (compared to 1.8 percent), and the authorities have requested an additional disbursement under the Rapid Credit Facility (RCF) of 50 percent of quota (SDR 122.2 million) under the 'exogenous shock' window of the RCF. This follows Board approval on April 3, 2020 of the authorities' request for 50 percent of quota, which took place before the annual access of the RCF was doubled to 100 percent of quota on April 6, 2020. This additional request, if approved, will bring total disbursements under the RCF to 100 percent of quota in 2020. The authorities have also requested temporary debt servicing relief under the G-20 Debt Service Suspension Initiative, supported by the G-20 and Paris Club.